Le ventre de Juliette - Provost, Martin; Abdelnour, Marc; Lasry, Philippe; Parmentier, Julie-Marie; Maura, Carmen, 1945- (Alta Loma Films, 2002)
Juliette, 20 years old, tries to come to terms with an unexpected pregnancy, despite a lack of support from the father of the child and from her mother. --